Tabula rasa - Carroll, David; Ward, Kyla Lee. ([Sutherland, N.S.W.] : David Carroll and Kyla Ward, 2001)
Web site maintained by David Carroll and Kyla Ward covering various subjects, including the history of horror and current developments, Australian genre fiction & films, and the authors'roleplaying projects. Site also includes online versions of the serials Burnt Toast and Tabula Rasa.
Title from title screen (viewed on Jan. 15, 2002).
Text and graphics.
Mode of access: Internet via World Wide Web. Available at: http://www.tabula-rasa.info
Site includes online versions of the serials Tabula rasa and Burnt toast.
Selected for archiving
Keywords: Fantasy games; Horror comic books, strips, etc. -- Australia; Horror films -- History and criticism; Horror tales -- History and criticism; Horror tales, Australian -- History and criticism; Horror; Australian